2016
DOI: 10.1097/aap.0000000000000406
|View full text |Cite
|
Sign up to set email alerts
|

The Analgesic Effect of Obturator Nerve Block Added to a Femoral Triangle Block After Total Knee Arthroplasty

Abstract: Addition of ONB to FTB significantly reduced opioid consumption and pain after TKA compared with a single FTB or LIA, without impaired ambulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 121 publications
(37 citation statements)
references
References 30 publications
0
36
1
Order By: Relevance
“…[50][51][52][53] A new study has compared the analgesic effect and opioid consumption of combined ultrasound-guided FT and subpectineal obturator nerve block versus FT block alone versus LIA in patients treated with multimodal analgesia after TKA. 36 The total intravenous morphine consumption during the first 24 postoperative hours showed a very large and significant reduction in the combined obturator nerve and FT blocks group compared to the other 2 groups-as well as reduced pain, nausea, and vomiting. The ambulation tests showed no difference between the groups.…”
Section: Strategy To Block Knee Pain From the Posterior Nerve Groupmentioning
confidence: 84%
See 1 more Smart Citation
“…[50][51][52][53] A new study has compared the analgesic effect and opioid consumption of combined ultrasound-guided FT and subpectineal obturator nerve block versus FT block alone versus LIA in patients treated with multimodal analgesia after TKA. 36 The total intravenous morphine consumption during the first 24 postoperative hours showed a very large and significant reduction in the combined obturator nerve and FT blocks group compared to the other 2 groups-as well as reduced pain, nausea, and vomiting. The ambulation tests showed no difference between the groups.…”
Section: Strategy To Block Knee Pain From the Posterior Nerve Groupmentioning
confidence: 84%
“…8, A and B). [34][35][36] The posterior branch of the obturator nerve can be blocked selectively in the subinguinal region between the adductor brevis and magnus muscles. 37,38 The anterior branch of the obturator nerve can be blocked selectively in the subinguinal region between the adductor brevis and longus muscles.…”
Section: Obturator Nerve Blockmentioning
confidence: 99%
“…Furthermore, the benefits stemming from obturator blockade also seems to extend to postoperative analgesic regimens using femoral triangle blocks. In 2016, Runge et al 380 compared femoral triangle blocks to combined femoral triangle-obturator blocks in patients undergoing TKR. These authors reported that the addition of obturator blockade resulted in decreased opioid consumption, pain scores and side effects (ie, nausea and vomiting).…”
Section: Controversial Areas Related To Outcomesmentioning
confidence: 99%
“…The significant reduction of motor control in the ONB group indicates that a significant fraction of subjects in the ONB group indeed had an ONB, although the motor control score was not intended as an assessment of the nerve block. Moreover, we used the exact same robust easy-to-perform method for ultrasound-guided subpectineal ONB as in a previous trial, where the efficacy of the technique was documented 15. Second, even though we took meticulous precautions to keep patients and staff blinded, some subjects may have become aware, that they had received an active ONB due to paralysis of the hip adductors.…”
Section: Discussionmentioning
confidence: 99%
“…Within 1 hour after end of surgery an ultrasound-guided proximal ONB was performed as previously described 15. A linear transducer (X-Porte, Fujifilm SonoSite, Bothell, Washington, USA) was oriented in the transverse plane and placed in the inguinal crease.…”
Section: Methodsmentioning
confidence: 99%